The Immunomodulatory Effect of Elephantopus scaber and Sauropus androgynus Extract to Cellular Immune Response in Pregnant Mus muscullus Infected by Salmonella typhimurium - Jannah, Nur; Djati, Moch. Sasmito; Widyarti, Sri (Graduate School, Universitas Brawijaya, 2016)
Pregnancy has a high risk and is more susceptible to infectious diseases. E. scaber and S. androgynus contains saponins and flavonoids as an immunomodulatory that can increase the body's immunity. The purpose of this study is to determine the immunomodulatory effects of E. scaber and S. androgynus leaf extract against cellular immune response in pregnant mice infected S. typhimurium. This research used seven treatment groups including negative control (K-) mice without injected S. typhimurium, positive control (K+) mice were injected S. typhimurium and extract treatment with 5 variant doses and dissected on the 12th and 18th days. Lymphocytes was isolated from the blood, then relative number of CD4+ and CD8+ were analyzed with flow cytometry and data continued with ANOVA. Statistical analysis showed that different extract dose and duration of treatment had a significant effect on the number of CD4+ and CD8+ T cells. E. scaber and S. androgynus act as immunomudulatory effect and treatment with combination of extracts E. scaber and S. androgynus 50 mg.kg-1 BW + 112.5 mg.kg-1 BW respectively and treatment with extract of S. androgynus 150 mg.kg-1 BW are the optimum treatment which can restore immune system conditions such as normal pregnancy without infection.Keywords: Cellular Immune, E. scaber, Immunomodulatory, S. androgynus, S. typhimurium.